anonymous
  • anonymous
Solve the following equation. 3(y – 5) + 2 = 5 (1 point) y = 4 y = 7 y = –4 y = 6
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
does anybody know this problem
anonymous
  • anonymous
Here:
1 Attachment
anonymous
  • anonymous
Solve the following equation. 3(y – 5) + 2 = 5 (1 point) y = 4 y = 7 y = –4 y = 6 18. Solve the following equation. 75 = –5(–3 – 4x) (1 point) x = 3 x = –4 x = –3 x = 5 19. Solve the following equation. –2x + 4 = 2(4x – 3) – 3(–8 + 4x) (1 point) x = 7 x = 2 x = –7 x = 3

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
does anyone know these
anonymous
  • anonymous
18-
1 Attachment
anonymous
  • anonymous
19-
1 Attachment
anonymous
  • anonymous
Are you not seeing the photos? Lol
anonymous
  • anonymous
yes
anonymous
  • anonymous
Solve the following equation. u + 2 = 4
anonymous
  • anonymous
is the answer 2 ?
anonymous
  • anonymous
Yes
anonymous
  • anonymous
Solve the following equation. –5 = s – 3
anonymous
  • anonymous
Add the 3 to both sides
anonymous
  • anonymous
So it will be: -2=s
anonymous
  • anonymous
Or you could flip it around if you are used to having the variable on the right side : s=-2 It's the same thing
anonymous
  • anonymous
*sorry the variable on the left side
anonymous
  • anonymous
Solve the following equation. five over thirteen t = –9
anonymous
  • anonymous
Is the t only with the 13, or with the whole fraction?
anonymous
  • anonymous
A or b
1 Attachment
anonymous
  • anonymous
a
anonymous
  • anonymous
A
anonymous
  • anonymous
Solve the following equation. 13 + w over 7 = –18

Looking for something else?

Not the answer you are looking for? Search for more explanations.